If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 2 = 6 + 9x Reorder the terms: 2 + 5x = 6 + 9x Solving 2 + 5x = 6 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 2 + 5x + -9x = 6 + 9x + -9x Combine like terms: 5x + -9x = -4x 2 + -4x = 6 + 9x + -9x Combine like terms: 9x + -9x = 0 2 + -4x = 6 + 0 2 + -4x = 6 Add '-2' to each side of the equation. 2 + -2 + -4x = 6 + -2 Combine like terms: 2 + -2 = 0 0 + -4x = 6 + -2 -4x = 6 + -2 Combine like terms: 6 + -2 = 4 -4x = 4 Divide each side by '-4'. x = -1 Simplifying x = -1
| (3y-9)(-2y^2+7y+1)= | | (3+5g)(2)= | | 4(g+4)=5(g-3) | | 2-4y+16=4 | | 4(9+5)=5(9-3) | | 3+6x=5x-4 | | -7x+10=90+x | | 4x^2+4v-1=0 | | (4x-5)(3x+7)=0 | | 8+2(z-4)=-3z+3 | | 2x+2=3(x+5) | | 3y-4x=-9 | | 68=-16t+64t+8 | | 6(9x-4)-(6x-12)= | | 3x^2-5=-53 | | -1x-7-2x=23 | | 6+x-5x=-26 | | 4x+1=3x+12 | | 4+x+5x=64 | | 3x-3=11x-5 | | 4y+7=9-2y | | 4(3y-7)+5= | | 6d^2+11d-3=0 | | 6d^2+21d=10d-3 | | -7(0)-9y=63 | | 3(5-6m)=39 | | -3(0)-7y=21 | | C(x)=60x+4000 | | -3x-4(-4x+6)=41 | | 2x+48=5x-3 | | x+3-3x-15=8 | | 8y+7=6y-3 |